FORMULASI SEDIAAN SHAMPO EKSTRAK ETANOL DAUN ADAM HAWA (Rhoeo discolor) SEBAGAI ANTIKETOMBE - Ginting, Ferdinand Paulus; Purba, Sondang; Ike Dameria Br Purba, Hana; Farhan, Reza (JURNAL TEKNOLOGI KESEHATAN DAN ILMU SOSIAL (TEKESNOS), 2021)
Background: Dandruff is a problem that is often experienced which is the role of microorganisms such as fungi. Pityrosporum ovale is a fungus that causes dandruff in hair. One way to increase activity is to make anti-dandruff shampoo preparations from adam hawa leaves which contain anthocyanins flavonoid compounds and leaf chlorophyll pigments that have antimicrobial activity. Methods: This type of research is an experimental study by conducting a preliminary test on the antifungal activity of the extract of the leaves of adam hawa (Rhoeo discolor) and continued with testing the antifungal activity of anti-dandruff shampoo preparations. The shampoo is made with a blank formula and with the best concentration of adam hawa leaf extract in inhibiting the fungus Pityrosporum ovale. Then the stability test was carried out by evaluating several parameters including organoleptic tests, pH tests, viscosity tests as well as high and foam stability tests. Results: The results showed that the leaf extract of adam hawa (Rhoeo discolor) had the best antifungal activity at a concentration of 90% and met the requirements of organoleptic test, pH test, high foam test and viscosity test. The presence of an inhibitory zone activity, the results of testing the antifungal activity of the shampoo preparations of adam hawa leaf extract (Rhoeo discolor) showed that the shampoo preparation with a concentration of 90% had antifungal activity although it was in the weak category and could be used as an anti-dandruff shampoo.